Evaluation of Interaction between Oxytetracycline and Aflatoxin B1-Induced Cytotoxicity - T. Jagadeesh; M. Parthiban; P. Raja; Ghadevaru Sarathchandra; S. Vairamuthu (The Indian Veterinary Journal, 2023)
To mitigate the toxicity of aflatoxin B1 (AFB1) in animals, additional therapeutic agents are needed due to the limitations of mycotoxin binders. AFB1-induced cytotoxicity is mediated by mitogen activated protein kinase pathways (MAPK). It has been reported that oxytetracycline (OTC) and its analogues have been shown to inhibit the activity of the MAPK pathway. Therefore, it is important to draw attention to this context to know the effect of OTC on AFB1-induced cytotoxicity. The results from molecular docking revealed that OTC interacted more positively with the MAPK1 protein. In vitro studies revealed that the 50μg/mL concentration of OTC effectively protects the cytotoxicity induced by AFB1 using MTT and Trypan blue techniques.